أثر الإبــداع في تحسین أداء المنظمات الحدیثة - بورنان , مصطفى (Finance and Business Economies Review, 2018)
Innovation and its access are considered as a vital and a fundamental device to promate the development of the economic entreprises and keep them in creasingly steady. Believing of the necessity of insisting on the reinforcement of the innovation policy and the creativity thought for the development sake to organize the economic and administrative purpose aiming at bettering the competence and efficiency of the entreprises.This study aims at the innovation for the understandings and the theories, their levels and their process i.e. their explanation and the factors effecting their economic and social policies.